Урал. Кладовая земли - Лаврова Светлана Аркадьевна (История России, 2009)
Экземпляры: ф.12 (2010) / Инвентарный номер: 53625 / Цена: / Сис.шифр: 26.8(2) / Авт.знак: Л 13 / ГРНТИ: 39.23.15 / ББК: 63.3(235.55)